In Vitro and In Silico Assessments of Curcuminoids and Turmerones from Curcuma longa as Novel Inhibitors of Leishmania infantum Arginase - Flora F. S. Spíndola; Anderson S. Pinheiro; Maria Athana Mpalantinos; Jefferson R. A. Silva; Walter S. M. F. Neto; Raissa A. Conceição; Eduarda M. Barreto; Barbara A. Abrahim-Vieira; Carlos R. Rodrigues; Alessandra M. T. Souza; Dirlei Nico; Ana Claudia F. Amaral; et al. (Pharmaceuticals, 2025)
Background/Objectives: The anti-Leishmania potential of Curcuma longa and its derivatives, such as curcuminoids, is well-established, yet their mechanisms of action remain underexplored. This study investigates the inhibitory effects of C. longa extracts and curcumin on Leishmania infantum arginase, a key enzyme in polyamine and trypanothione biosynthesis, and evaluates their antiparasitic activity. Methods: Extracts were prepared via rhizome successive maceration with hexane (HEXCURC), dichloromethane (DCCURC), and ethanol (ETOHCURC) and chemically characterized by a combination of chromatographic and spectrometric methods. The inhibition of recombinant L. infantum arginase (LiARG) was assessed by urea quantification, while molecular docking explored interactions between the main compounds annotated in the extracts and the enzyme’s active site. Biological activity was tested against L. infantum promastigotes, intracellular amastigotes, and mammalian cells. Results: LC-MS and GC-MS revealed curcuminoids and turmerones as main compounds annotated in the extracts. DCCURC, HEXCURC, and curcumin showed the strongest LiARG inhibition (IC50 = 10.04, 14.4, and 17.55 μg/mL, respectively). Docking analysis revealed that curcumin, demethoxycurcumin, and bisdemethoxycurcumin bind near the active site, with binding energies of –3.43, –4.14, and –3.99 kcal/mol, respectively. Curcumin demonstrated superior anti-promastigote activity (IC50 = 15.01 μg/mL) and selectivity (SI = 12.7) compared to the extracts. It also significantly reduced amastigote burden in infected macrophages (IC50 = 13.6 μg/mL). Conclusions: This is the first report demonstrating that C. longa extracts and curcumin inhibit LiARG. These findings support curcumin’s potential as a lead compound for developing multi-target therapies against leishmaniasis, combining enzyme inhibition with direct antiparasitic effects.